Evapotranspiration Estimates in Different Semi-Arid Municipalities of Northeastern Brazil Under Drought Scenarios - Cattani , Bianca Carolina Bernardin; Araújo, Ana Beatriz Alves de; Morais, Luara Lopes; Santos, Liherberton Ferreira dos; Sobrinho, José Espínola; Pordeus, Roberto Vieira; Silva, Saulo Tasso Araújo da; Batista, Rafael Oliveira; Souto, Antônio Gustavo de Luna; Antunes, Luiz Fernando de Sousa (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
Estimating evapotranspiration is an excellent tool for developing studies and activities aimed at water use and water resource management projects, especially in regions of water scarcity. This work aimed to evaluate the performance of more simplified and practical methods for estimating evapotranspiration in different regions of the state of Rio Grande do Norte under different climatic conditions, using the Penman-Monteith-FAO56 method as a standard model. The methods tested were: Linacre (1993), Priestley-Taylor (1972), Souza-Silva (2022) and Solar Radiation. Climatological data from the microregions of Macau, Mossoró and Western Seridó were used from 2007 to 2019. The Linacre model (1993) presented the best performance in the regions evaluated and can be recommended in different climatic conditions of the year.